Jezus, de unieke drager van Gods Geest - G. D. J. Dingemans (Acta Theologica)
Research of the “historical Jesus” has produced a considerable number of books and articles, but has not given us a reliable view on Jesus. Scholars do not get further than Jesus as a charismatic teacher. The “traditional Christ of the church” with the doctrine of the two natures causes many problems for modern man because of the old philosophic framework and its static character. In my opinion a linguistic analysis of the New Testament shows that the witnesses of Jesus were deeply impressed by the mystery of Jesus’ charismatic appearance, both during his lifetime and after his death. In his attitude, his words and activities they have experienced the real presence of God. For all of the authors of the New Testament the divine presence culminated in the experience of the Risen Lord. To express that mystery I plead for a kind of “pneuma-christology”: Jesus was born as a human being and he received the Holy Spirit as he was baptised by John the Baptist — as most of the Gospels tell us. Especially after his death and resurrection the Risen Lord works in the world as the Spirit of Christ. Christ is the human face of God. A pneumachristology is more dynamic than the doctrine of the two natures and gives more room for the idea that Jesus was a real man (vere homo). At the same time the experience is expressed that in him God himself (vere Deus) — in the shape of the Holy Spirit — was active in a complete and absolute way. In that way he was the unique Bearer of the Holy Spirit — in contrast with other bearers of the Spirit like prophets and apostles.